Treinamento corporativo: gamificação, engajamento e motivação nos ciclos de aprendizado - Marangoni, Matheus Matsuda (2022)
This thesis was grounded on the identification of the evolution of gamified tools as strategies to increase engagement in corporate training and learning processes in general. Over the last few years, the theme of gamification has been gaining ground in the corporate world, especially in terms of human development. It is also understood that the advancement of technology and the changes in career prospects of individuals have generated the need for new ways of engaging and motivating employees in their personal and professional development. Therefore, to understand how gamified solutions are built and what benefits they present, the following basis were used: perspectives of intrinsic motivations linked to career anchors (SCHEIN, 1978), selfdetermination motivations (RYAN and DECI, 2000a), and motivations worked by gamification (PAHARIA, 2013) aligned with four gamification frameworks: 6Ds (WERBACH and HUNTER, 2020), MDA (HUNICKE, LEBLANC and ZUBEK, 2004), Octalysis Framework (CHOU, 2019) and Game Design Toolkit (MARCZEWSKI, 2017). To represent and validate the studied theories, three case studies of large Brazilian companies are presented. The main findings are the understanding of replicable processes through frameworks and the relevance of applying the intrinsic motivations associated with the use of gamification